2012
DOI: 10.1074/jbc.m111.282533
|View full text |Cite
|
Sign up to set email alerts
|

Microcin Amyloid Fibrils A Are Reservoir of Toxic Oligomeric Species

Abstract: Microcin E492 (Mcc), a low molecular weight bacteriocin produced by Klebsiella pneumoniae RYC492, has been shown to exist in two forms: soluble forms that are believed to be toxic to the bacterial cell by forming pores and non-toxic fibrillar forms that share similar biochemical and biophysical properties with amyloids associated with several human diseases. Here we report that fibrils polymerized in vitro from soluble forms sequester toxic species that can be released upon changing environmental conditions su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 40 publications
3
71
0
2
Order By: Relevance
“…S1). Previous studies have shown that fibrils can serve as reservoirs of toxic oligomers (38,39). Because of the relative instability of out-ofregister fibrils, we hypothesize that they are more prone to release oligomers than in-register fibrils.…”
Section: Discussionmentioning
confidence: 91%
“…S1). Previous studies have shown that fibrils can serve as reservoirs of toxic oligomers (38,39). Because of the relative instability of out-ofregister fibrils, we hypothesize that they are more prone to release oligomers than in-register fibrils.…”
Section: Discussionmentioning
confidence: 91%
“…Fap fibrils have been shown to bind extracellular metabolites within the biofilm, such as quorum-sensing molecules and redox mediators, modulating their release and retention when required. This implies a potential new role for functional amyloids in molecular retention and indirect mediation of cell function (7,39,40) Again, genes encoding proteins with homology to the Fap systems are present within species belonging to the Beta-, Gamma-, and Deltaproteobacteria (38).…”
Section: Amyloid Structures With Dedicated Fiber Assembly Machinerymentioning
confidence: 99%
“…However, numerous pieces of evidence indicate that amyloid fibers are not just the result of aberrant protein folding but are produced on purpose under different nonpathological conditions to provide organisms with beneficial properties (3). The microbial world makes use of this type of protein folding for a number of processes relevant for bacterial growth and survival in the environment, such as morphological differentiation of filamentous bacteria (4,5), adhesion to host tissues (6), detoxification of toxic compounds (7)(8)(9), electron transport (10), and structural scaffolds in biofilm matrices (1).…”
mentioning
confidence: 99%
“…Indeed, it has been reported that the number of b-cells is selectively decreased in islets containing IAPP aggregates (Jurgens et al 2011). It is interesting to note that our own studies have shown that large amyloid fibrils are able to release oligomers capable of forming seeds under physiological conditions (Shahnawaz and Soto 2012). Based on the findings obtained in other PMDs, it seems possible that IAPP aggregates may be able to propagate from b-cell to b-cell and perhaps even from islet to islet.…”
Section: Spreading Of Protein Aggregates Within Affected Tissue and Imentioning
confidence: 82%